Microstructure and mechanical characterisation of ZrO2 reinforced Ti6Al4V metal matrix composites by powder metallurgy method. (1st February 2022) - Haja Syeddu Masooth, P; Bharathiraja, G; Jayakumar, V; Palani, Kumaran
Abstract: This study investigated the mechanical and microstructural properties of ZrO2 reinforced titanium metal matrix composites (TMMCs) fabricated using powder metallurgy. The base matrix of the Ti6Al4V alloy was reinforced with ZrO2 at mixing proportions of different wt percentage points at 0, 3, 4, 5 and 6. Microstructure evaluation was carried out to study the bonding characteristics of the matrix and reinforcement, and it was confirmed that the reinforcement was homogenously mixed with the base matrix. The objective is to study the effect of zirconia on mechanical properties such as hardness, compression strength and thermal expansion coefficiency of Ti6Al4V alloy. The hardness, compression strength, and shrinkage rate are increased with the increase of ZrO2 . Finally, it was observed that, 6 wt percentage of ZrO2 reinforced composite showed better characteristics in that the hardness and compression strength were the highest among all the proportions used and the coefficient of thermal expansion was low. Due to these promising results, the fabricated ZrO2 reinforced Ti6Al4V composite can be a potential material for structural, aerospace and automotive applications.